Evaluation as a feed back and accountability mechanism: the theory and a trail (2006)
This paper discusses the concepts of evaluation, feedback and accountability and shows how evaluation is a means to both feedback and accountability. Evaluation implies verification of the true state of programme implementation while accountability stresses efficiency of the programme and takes off from where evaluation ends. Feedback however deals with the information, which could be used to improve a programme performance. However, the paper further shows that evaluation as an accountability mechanism reveals the strength or weaknesses or opportunties of a programme or the threats to the programme. As a feedback mechanism, evaluation facilitates decision-making process and improvement of a programme. The study also reveals that somtimes evaluation data are neither used as feedback nor accountability mechanism and suggest that evaluation data should be utilized for feedback or accountability purposes. The result of the study is that evaluation as both accountability and feedback mechanism improves teaching/learning process as well as students performance.